Estudo sobre a trajetória da assistência social no Brasil : do padrão assistencialista ao profissionalizado - Silva, Juliana de Araujo (2017)
This paper aims to bring contributions to studies on Social Assistance in Brazil. The main objective is to analyze the main Social Assistance organizations in the process of identity construction as public policy in the Socio-Social Network of São Carlos / SP, that is, to identify the changes that occurred in Social Assistance of the traditional model (optics by Charity / welfare) to the New Social Assistance (optic of rights / non-contributory) as the organizations of public and private origin were structured, or better structured. Do these places, after 28 years of the institution of Social Assistance as a social right, have been modified / incorporated these new socio-welfare practices, or not? The sketch took place in two phases, in the first phase, through a bibliographical survey about the historical events up to the present of the trajectory of Social Assistance in Brazil, analyzing how these events impacted on the transformations that took place inside the social assistance organizations producing the reality in the Which we live. The second phase, called field research and data analysis, took place in the units of the Reference Center on Social Assistance - CRAS, a unit of Specialized Referral Center in Social Assistance - CREAS, a unit of the Specialized Reference Center for People in Situation Rua - Centro Pop, and in nine regulated social entities in the Municipal Council of Social Assistance of São Carlos. Data collection took place through interviews with the organization's staff: social workers, psychologists and coordinators, as well as observation and documentary analysis.